The Origin and Importance of Freinet Research Team in the Innovation Movement of Early Childhood Education During the Middle of 1980s (Training and Practice : Journal of Educational Sciences, 2012)
Democratic changes in the middle of the 1980s provoked paradigmatic turn in early childhood education as well; providing an innovation movement of pedagogical practise. Leaving the former methods behind, by the opportunity of alternativity and pluralism, educators and kindergarten-teachers tried to search new ways of children-based pedagogical techniques. In this period, a research team was founded at Kindergarten Teachers Training College of Sopron implementing the pedagogy of the French educator, Célestin Freinet, with the purpose of guaranteeing children’s right to self-expression and underpinning the importance of cooperation, individual and social development and differences. The principal aim of this study is representing the significance and relations network of Freinet Research Team in the innovation movement of early childhood education and care.